Articles of Agreement of the International Monetary Fund - International Monetary Fund; International Monetary Fund (Washington, D.C. : International Monetary Fund, 1969)
This book is the article of agreement by IMF to enable the fund to conduct its operations and transactions.
Includes index.
osc 1/12/16, rua 21/04/17
Loans
Keywords: International Monetary Fund